Demographics Municipal Karrada year (2012-2013) (Journal of the College of Education for Women, 2019)
The study aims to identify the reality of educational services in the municipality of Karrada described in this disclosure about the reality of the distribution of educational services and appropriate that the distribution with the population density in the region, both quantitatively and qualitatively, as are educational services an event practiced by the cities and provided to the population, it has a significant impact on the cultural development of society.